Second International Handbook on Globalisation, Education and Policy Research
XXXIV, 854 p. 28 illus.
Keywords: This handbook presents a global overview of developments in education and policy change during the last decade. It provides an accessible, practical and comparative source of current research that examines the intersecting and diverse discourses of this important issue. Divided into two parts, the handbook first examines globalisation and education policy reforms, including coverage of main trends as well as specific policy issues such as gender, equity, minorities and human rights. Next, the handbook offers a comparative perspective that evaluates the ambivalent and problematic relationship between globalisation, the state and education reforms globally. It features coverage on curricula issues and education reforms in schools around the world as well as the curriculum in the global culture. Now more than ever there is a need to understand and analyse both the intended and the unintended effects of globalisation on economic competitiveness, educational systems, the state and relevant policy changes - all as they affect individuals, the higher education sector, schools, policy-makers and powerful corporate organisations across the globe. By examining some of the major education policy issues, particularly in the light of recent shifts in education and policy research, this handbook offers readers a comprehensive picture of the impact of globalisation on education policy and reforms. It will serve as a vital sourcebook of ideas for researchers, practitioners and policy makers in education.